Organizational communication effectiveness, a research in banking sector - Özarallı, Nurdan (My University, 1995)
unknown
Keywords: ETKİNLİK-ÖRGÜTLER; Genel yönetim; İletişim; İLETİŞİM-ÖRGÜTLER; Yürütmenin yönetimi